2022
DOI: 10.22202/jg.2022.v8i1.5699
|View full text |Cite
|
Sign up to set email alerts
|

Revitalization of Batak Toba Cultural Identities Used Language as Communication in the Sianjur Mula-Mula, Samosir Regency

Abstract: At the moment, there are indications that the Toba Batak people of Sianjur Mula-Mula District have disregarded the sociocultural values embodied in indigenous wisdom regarding the protection of Lake Toba. The deterioration of sociocultural values has increased environmental damage to Lake Toba, which is currently escalating. This study aims to examine how Toba Batak sociocultural values can be revitalized to protect the Lake Toba environment in Sianjur Mula-Mula Regency. The descriptive qualitative method with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…This phenomenon is because the older generation needs to pass on the mantra, symbols, and rules used in each Mandiu Pasili traditional ritual procession to the younger generation. It is consistent with the study by Napitu (2022) on Lake Toba protection, which showed that the community had disregarded the sociocultural values enshrined in the initial policy designed to protect the lake. As a result, local cultures have suffered more harm as their sociocultural values have been eroded.…”
Section: Introductionsupporting
confidence: 89%
“…This phenomenon is because the older generation needs to pass on the mantra, symbols, and rules used in each Mandiu Pasili traditional ritual procession to the younger generation. It is consistent with the study by Napitu (2022) on Lake Toba protection, which showed that the community had disregarded the sociocultural values enshrined in the initial policy designed to protect the lake. As a result, local cultures have suffered more harm as their sociocultural values have been eroded.…”
Section: Introductionsupporting
confidence: 89%